1994
DOI: 10.1021/ef00047a013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reaction between zinc oxide and hydrogen sulfide

Abstract: The reaction between zinc oxide and hydrogen sulfide was studied in the presence of coalderived gases. The reaction was inhibited by the presence of H2O. The effect of CO2 on the reaction was smaller than that of H2O. H2 accelerated the reaction at 500 °C and inhibited it at 400 °C in the presence of H2O. CO also inhibited the reaction in the presence of H2O. COS was formed from H2S and CO in the absence of H2. Elemental sulfur was formed from COS only under the H2S-N2 system. In explanation of the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 3 publications
6
41
1
Order By: Relevance
“…Davidson et al [11] reported about 40% conversion of ZnO on the adsorption of H 2 S over ZnO. Sasaoka et al [12] studied the adsorption of H 2 S on ZnO in the presence of CO, CO 2 and H 2 O, and found that CO and H 2 O inhibited the removal of H 2 S by occupying active sites and reversing the reaction between H 2 S and ZnO. In the range of 25-100°C, Carnes and Klabunde [13] found the activity of nanocrystalline metal oxides prepared by a sol-gel method decreased in the order of ZnO [ CaO [ Al 2 O 3 [ MgO.…”
Section: Introductionmentioning
confidence: 99%
“…Davidson et al [11] reported about 40% conversion of ZnO on the adsorption of H 2 S over ZnO. Sasaoka et al [12] studied the adsorption of H 2 S on ZnO in the presence of CO, CO 2 and H 2 O, and found that CO and H 2 O inhibited the removal of H 2 S by occupying active sites and reversing the reaction between H 2 S and ZnO. In the range of 25-100°C, Carnes and Klabunde [13] found the activity of nanocrystalline metal oxides prepared by a sol-gel method decreased in the order of ZnO [ CaO [ Al 2 O 3 [ MgO.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Numerous studies have been carried out on the kinetics and mechanisms of the interaction between ZnO and hydrogen sulfide [22][23][24][25][26][27][28]. Mechanisms of zinc sulfidation consisting in surface adsorption of gaseous H 2 S on ZnO sorbent and dissociation of the H 2 S molecule on the sorbent surface, followed by reversible surface reactions, sulfide ion migration under the surface and penetration of sulfide into the solid crystallite were proposed in [25].…”
Section: Introductionmentioning
confidence: 99%
“…A size effect of ZnO particles influencing the rate of zinc sulfidation was described in [26]. The DFT calculations showed [28] In [22,23] it was determined that increase in H 2 O concentration decreases the H 2 S capture and can cause the release of previously captured H 2 S, because of a shift in the equilibrium of the reaction (3) toward ZnO and H 2 S.…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods to remove hydrogen sulfide from gas streams which fall into three major categories: chemical reaction methods, absorption methods and adsorption methods. Today, the most conventional processes to remove hydrogen sulfide are amine aqueous solutions, Claus process and the liquid redox process [1][2][3].…”
Section: Introductionmentioning
confidence: 99%